Malonaldehyde Level of Administration Ethanol Extract of Purple Sweet Potato Var. Ayamurasaki in Doca-Salt Hypertensive Rats - Rahmawati, Irma Sarita; Soetjipto, Soetjipto; Adi, Annis Catur; Aulanni’am, Aulanni’am (Dept. Food Technology, Faculty of Animal and Agricultural Sciences, Diponegoro University, 2018)
There is an increasing amount of evidence that oxidative stress related to hypertension can damage the function of diverse structures such as aorta. It is a well-established fact that chlorogenic acid and anthocyanine found in purple sweet potato generates bioactive compound with antihypertensive and antioxidant activities. The present study sought to investigate antioxidant activity of extract ethanol of purple sweet potato (EP) in deoxycorticosterone acetate (DOCA–salt)–induced hypertensive rats (Rattus norvegicus). The rats were orally administrated a 95% ethanol extract of purple sweet potato (var. Ayamurasaki) (EP) in a daily dose of 200 and 400 mg/kg body weight for 4 weeks. Aorta total malondialdehyde (MDA) and histopathology of aorta abdominal were examined. Aorta injury was observed in DOCA-salt hypertensive group rats compared to normotensive group rats, as aorta MDA significantly increased (P<0.05). In contrast, treatment of DOCA-salt hypertensive rats with different dose of EP significantly reduced the total aorta MDA, as well as repair kidney damage, suppressed smooth muscle cell proliferation and lessen aorta wall thickening compared to controls. This is the first report that demonstrated blood pressure lowering and antioxidative effects of an ethanol extract of purple sweet potato, containing chlorogenic acid, in a DOCA–salt model of hypertension.